KINETICS OF GLICLAZIDE AFTER SINGLE DOSE ORAL ADMINISTRATION OF GLICLAZIDE 60 MG MODIFIED RELEASE TABLET - POP, Diana Ioana; MARCOVICI, Adriana; OROIAN, Monica; GHELDIU, Ana-Maria; VLASE, Laurian (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The current study aimed to establish and describe the basic pharmacokinetics of a single dose of gliclazide 60 mg modified release formulation manufactured by Ranbaxy Laboratories Limited, now Sun Pharmaceutical Industries Limited, India. Ten mathematical models were created for analyzing the experimental data resulted from two bioequivalence studies conducted at Clinical Pharmacology and Pharmacokinetics Department of Terapia S.A. Model discrimination was done using the Akaike index value and it was observed that model number 10 (M10) is the model that best describes the gliclazide disposition. This model has two compartments (peripheral and central), mixed order absorption process (1st and zero order kinetics) with a lag time of around 3 hrs and 1st order kinetics of elimination. Applying this model in Phoenix software version 6.3 (Pharsight Corp., Mountain view, CA, USA) the main pharmacokinetic parameters of gliclazide were also computed.